2018
DOI: 10.24275/uam/izt/dcbi/revmexingquim/2018v17n2/martinezd
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Gradients Application for Accelerating Corn Hydration

Abstract: Three varieties of corn kernels were hydrated under pressure gradients in the range of 96 to 136 cm Hg, and at atmospheric pressure for comparison. Hydration at atmospheric pressure was modeled by the first order kinetics model and by the Fick's second law of diffusion. Rate constants of 0.192, 0.184 and 0.141 h −1 , and water effective diffusivity of 5.4 ×10 −11 , 3.6 ×10 −11 , and 1.9 ×10 −11 m 2 s −1 were obtained for blue, yellow and white corn kernel, respectively. Significant polynomial equations describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Moreover, to obtain an average final moisture content of 0.7121 g H 2 O/g dry matter, DIC 17 and DIC 18 required 2 h instead of 17 h for controls. Similar results were found by Martínez-Garza [ 42 ] for blue, yellow, and white non-treated maize kernels which required 15 h of rehydration to achieve equilibrium moisture contents of 0.5270, 0.5000, and 0.5040 g H 2 O/g dry matter, respectively. This result reflects that DIC treatment intensified both rehydration stages, the starting accessibility and diffusional stages.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, to obtain an average final moisture content of 0.7121 g H 2 O/g dry matter, DIC 17 and DIC 18 required 2 h instead of 17 h for controls. Similar results were found by Martínez-Garza [ 42 ] for blue, yellow, and white non-treated maize kernels which required 15 h of rehydration to achieve equilibrium moisture contents of 0.5270, 0.5000, and 0.5040 g H 2 O/g dry matter, respectively. This result reflects that DIC treatment intensified both rehydration stages, the starting accessibility and diffusional stages.…”
Section: Discussionsupporting
confidence: 88%
“…However, this process used to be long which could cause microbial spoilage, swelling, and physical destruction of the food [ 41 ]. According to Martínez-Garza [ 42 ], obtaining a complete rehydrated grain sometimes requires 16–36 h, indicating that new technologies are needed to accelerate this process. In this respect, this study showed that the DIC technology could significantly improve the rehydration of maize kernels.…”
Section: Discussionmentioning
confidence: 99%
“…The Control samples showed a Deff value of 0.091 x 10 -9 ± 0.016 x 10 -9 m 2 /s. The obtained results were higher than reported by Martínez-Garza, et al [27] for white corn with Deff of 0.019 x 10 -9 m 2 /s, it is possible because of the different maize variety. Compared to control, the Deff value was significantly (p > 0.05) higher for ash treatment, it increased the Deff in about 354% (Table I).…”
Section: A Rehydration Kinetics Description Trough Mathematical Model...contrasting
confidence: 75%
“…The kinetic parameter of first-order model (𝑘 6 ) indicates the rate of rehydration, which is proportional to a temporary driving force. The 𝑘 6 values for Control samples (0.003 min -1 ) were between the values reported by Martínez-Garza, et al [27] for white corn (0.0024 min -1 ) or for yellow corn (0.0046 min −1 ) reported by Miano, et al [33]. Compared to Control, only the 𝑘 6 value for ash treatment was significantly different and was the highest, indicating higher rehydration rate in these samples.…”
Section: First-ordersupporting
confidence: 62%
“…The temperature measurement has been commonly carried out on the alkaline solution and its control is important due to its effect on quality parameters such as moisture and texture of masa, moisture and texture of tortilla, percentage and diffusion of calcium and solids loss (Sahai et al, 2001). Some reports have focused on mass transport phenomena in hydration of the corn kernel (Martínez-Garza et al, (2018)), and nixtamalization process, during cooking and steeping (Ruiz-Gutiérrez et al, 2010;Gutiérrez-Cortez et al, 2016); however, there are no studies about the behavior of temperature and heat transfer inside the corn kernel subjected to the nixtamalization process. In this operation, two unsteady state heat transfer mechanisms are involved: conduction inside the corn kernel and convection by the alkaline solution at the surface.…”
Section: Introductionmentioning
confidence: 99%